Rationale, Instrumental Accuracy, and Challenges of PET Quantification for Tumor Segmentation in Radiation Treatment Planning - Kirov, Assen S.; Schmidtlein, C. Ross; Kang, Hyejoo; Lee, Nancy (IntechOpen, 2012)
None